A comparison of leg stiffness in running between typically developing children and children with cerebral palsy. (April 2021) - Chappell, A.; Allison, G.T.; Gibson, N.; Williams, G.; Morris, S.
Abstract: Background: Leg stiffness is important during running to increase velocity and maximise efficiency by facilitating use of the stretch-shortening cycle. Children with cerebral palsy who have neuromuscular impairments may have altered leg stiffness. The aim of this study was to describe leg stiffness during running in typically developing children and those with cerebral palsy in Gross Motor Function Classification Scale levels I and II at a range of speeds. Methods: This cross-sectional study examined kinematic data collected from typically developing children ( n = 21) and children with cerebral palsy (Gross Motor Function Classification Scale level I n = 25, Gross Motor Function Classification Scale level II n = 13) during jogging, running and sprinting. Derived variables were resultant ground reaction force, change in leg length and three-dimensional leg stiffness. Linear mixed models were developed for statistical analysis. Findings: Children with cerebral palsy had reduced stiffness when jogging (Gross Motor Function Classification Scale level I affected t = 3.81 p < 0.01; non-affected t = 2.19 p = 0.03; Gross Motor Function Classification Scale level II affected t = 2.04 p = 0.04) and running (Gross Motor Function Classification Scale level I affected t = 3.23 p < 0.01) compared to typically developing children. Affected legs were less stiff than non-affected legs only in Gross Motor Function Classification Scale level I during running ( t = 2.26 p = 0.03) and sprinting ( t = 2.95 p < 0.01). Interpretation: Children with cerebral palsy have atypical leg stiffness profiles which differ according to functional classification. Highlights: Leg stiffness is reduced in jogging and running in children with cerebral palsy. Leg stiffness is reduced in affected legs compared to non-affected legs. Leg stiffness profiles differ according to gross motor functional classification.